Synthesis of Some Novel Sulfur Containing Triazolothienopyrimidines and Biscompounds as Possible Antitumor and Radioprotective Agents - Heiba, Helmy I.; Ragab, Fatma A.; Noaman, Eman; Ghorab, Moustafa M.; Galal, Marwa (Arzneimittelforschung, 2006)
The syntheses of novel 1,2,4-triazolothi-enopyrimidine derivatives (4a,b), thiourea derivatives (5-8) and biscompounds having a thieno[2,3-d]pyrimidine nucleus (13-16) utilizing the 2-isothiocyanato derivatives 2a,b are reported. The structures of these compounds were confirmed by microanalysis, IR, 1H-NMR and mass spectrometry. Preliminary biological studies of some synthesized compounds showed promising antitumor and radioprotective activities.
Keywords: Antitumor agents; Radioprotective agents; Thieno[2,3-d]pyrimidines, antitumor and radiopro-tectice action, synthesis